Testing convergence of fiscal policies in regions of Turkiye - Göksel Karaş; Ebru Karaş (Ekonomika, 2023)
The presence of convergence in the fiscal policies implemented at the national level to eliminate regional disparities is an indication that the resources are rationally distributed among the regions, and the disparities are decreasing. From this point of view, this study aims to investigate the convergence of the fiscal policy implemented in the period of 2004:01-2020:12 in Turkiye within the scope of the fiscal aim of taxes. The research methodology includes the evaluation of structural convergence between regions in Turkiye to reveal similar and different aspects of fiscal aim through the Panel Threshold Unit Root Test (Panel TAR) and Evans-Karras linearity convergence test. In the study, nonlinear convergence analysis was performed, but linear convergence analysis was used because the linearity hypothesis could not be rejected. According to the findings, there is an absolute convergence among the regions in the fiscal policy implemented in Turkiye. However, in terms of regions, the first region is differentiated from the other five regions, while the other regions are very close to each other. Regarding this, it may be possible to bring the first region and the other five regions closer to each other by reducing the disparity in the arrangements made in taxation policies. It should be aimed that each region has a comparative advantage according to its characteristics by implementing an effective policy to eliminate the disparities between regions.
Keywords: 330; convergence; fiscal aim; fiscal policy; region; Turkiye